2015
DOI: 10.1037/hea0000138
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistically observed conflict and youth asthma symptoms.

Abstract: Objective To investigate the links between naturalistically-observed conflict, self-reported caregiver-youth conflict, and youth asthma symptoms. Method Fifty-four youth with asthma (aged 10-17) wore the Electronically Activated Recorder (EAR) for a 4-day period to assess interpersonal conflict and caregiver-youth conflict as they occur in daily life. Conflict also was assessed with baseline self-report questionnaires and daily diaries completed by the youth participants and their caregiver. Asthma symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 53 publications
4
30
1
Order By: Relevance
“…Although the inter-rater reliabilities of the specific EAR conflict codes all within acceptable limits (e.g., above .70 for 2,k), the alpha levels for the caregiver-youth conflict composite was low due to small correlations between youth yelling ( r = .13, p = .40) and mother yelling ( r = .15, p = .35) with mother-youth conflict. However, in previous work, we identified that the yelling codes were significantly correlated with youth daily reports of negative caregiver-youth interactions (31). Thus, on both theoretical grounds and for parsimony of conducting analyses, we retained the yelling codes in the conflict composite.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Although the inter-rater reliabilities of the specific EAR conflict codes all within acceptable limits (e.g., above .70 for 2,k), the alpha levels for the caregiver-youth conflict composite was low due to small correlations between youth yelling ( r = .13, p = .40) and mother yelling ( r = .15, p = .35) with mother-youth conflict. However, in previous work, we identified that the yelling codes were significantly correlated with youth daily reports of negative caregiver-youth interactions (31). Thus, on both theoretical grounds and for parsimony of conducting analyses, we retained the yelling codes in the conflict composite.…”
Section: Methodsmentioning
confidence: 77%
“… 1 Other papers from the same project have examined naturalistically observed conflict and asthma symptoms (31) and socioeconomic status and youth behaviors (32). The present analyses do not overlap with analyses from those other papers.…”
mentioning
confidence: 99%
“…19 A few studies have used the EAR with children, including in the context of health research. [20][21][22][23][24] The EAR has specific advantages for child research: it does not require the capacity to read or understand questions posed in questionnaires or to maintain attention during interviews. 25 Likewise, it does not rely on retrospective accounts of behaviour.…”
mentioning
confidence: 99%
“…In recent years, however, researchers have shifted their focus toward understanding the positive characteristics that shape family relationships (Kim, Haskett, Longo, & Nice, 2012; Tobin et al, 2015). Such research is necessitated by the fact that romantic relationship conflict does not indicate the absence of positive features in the relationship per se (Christensen & Walczynski, 1997).…”
mentioning
confidence: 99%
“…Given the evidence that points to detrimental effects of negative family characteristics, it is important for researchers to identify positive aspects of family life that may serve as resource factors or mitigate asthma exacerbations. Emerging work points to beneficial relationships between maternal responsiveness and warmth with asthma related immune processes (Chen, Miller, Kobor, & Cole, 2011; Tobin, et al, 2015). A more comprehensive approach that assesses parental romantic relationships from the youth perspective may provide more insights into the influence of family environment on asthma morbidity.…”
mentioning
confidence: 99%